NONLINEAR COMPOSITION DEPENDENCE OF MOLAR VOLUME OF MELTS IN THE CAO-AL2O3-SIO2 SYSTEM - Courtial P.; Dingwell D.B. (My University, 1995)
Density measurements have been performed on nine liquids in the system CaO-Al2O3-SiO2, in the temperature range of the melting point up to 1800°C, using both Pt- and Ir-based double-bob Archimedean method. In addition, the molar volume has been determined at 1800°C for one liquid along the SiO2-Al2O3 join. The data of this study show that, within the temperature and the composition range investigated, the molar volume of Ca-aluminosilicate melts at low SiO2 content does not behave linearly as function of the composition. This nonideality results clearly from interaction between SiO2 and CaO, whereas our data in addition with literature data suggest that SiO2-Al2O3 and CaO-Al2O3 interactions could also occur in these Ca-aluminosilicate melts at high Al2O3 content.These different results were analysed using a regression equation from which the partial molar volume of each component was obtained by the method of least squares. A nonideal model (SC) for Ca-aluminosilicate melts is thus proposed, involving an excess volume term between SiO2 and CaO and leading the calculation of the liquids molar volume within 0.5% of uncertainties except for Ca- and Al-rich compositions. A better constrain of this model in this extreme composition range requires new data of pure alumina liquid. Some structural implications of this nonideal behaviour with respect to the molar volume are also discussed.